Types of intelligence in engineers of the Norte de Santander Department-Colombia (2020)
The research had the objective of determining the types of intelligence that public servants in the Department of Norte de Santander, Colombia possess, building a model in which intelligence is associated with the variables of transparency, integrity, communication, competence, organizational climate, security, trust and ethical orientation, which public servants should have. A mixed study was undertaken to study these variables, and their association to the types of intelligence. Interviews were applied and a non-experimental factorial design was used with support in two questionnaires, whose validity was high with a Kappa index of 0.78 obtained through the evaluation of experts, and a reliability with Cronbach's Alpha of 0.85. The population was focused on 500 public servants with engineering degrees who work in the metropolitan area of Cúcuta, Ocaña, Patios, Sardinata and Cacota, selecting a sample of 110 officials. The results allow the identification of 8 types of intelligence and 42 emerging categories of skills associated with these types of intelligence in public service engineers. The quantitative factorial confirmatory analysis shows four intelligence models, in which emotional, cognitive-rational, social and creative intelligence have greater weight, the most preponderant being emotional intelligence.